An allosteric switch-based hairpin for label-free chemiluminescence detection of ribonuclease H activity and inhibitors. Issue 4 (4th January 2019) - Zhou, Ying; Zhang, Jingjing; Jiang, Qian; Lu, Jianzhong
Abstract : To assay enzyme activities and screen its inhibitors, we demonstrated a novel label-free chemiluminescent (CL) aptasensor for the sensitive detection of RNase H activity based on hairpin technology. Abstract : To assay enzyme activities and screen its inhibitors, we demonstrated a novel label-free chemiluminescent (CL) aptasensor for the sensitive detection of RNase H activity based on hairpin technology. The specific hairpin structure was a DNA–RNA chimeric strand, which contained a streptavidin aptamer sequence and a blocked RNA sequence. RNase H could specifically recognize and cleave the RNA sequence of the DNA–RNA hybrid stem, liberating the streptavidin aptamer which could be accumulated by streptavidin-coated magnetic microspheres (SA-MP). Then the CL signal was generated due to an instantaneous derivatization reaction between the specific CL reagent 3, 4, 5-trimethoxyphenyl-glyoxal (TMPG) and the guanine (G) nucleotides in the SA aptamer. This novel assay method exhibited a good linear relationship in the range of 0.1–10 U mL −1 under the optimized conditions. Our results suggested that the developed system was a promising platform for monitoring the RNase H activity and showed great potential in biomedical studies and drug screening.